Thermal and hydraulic analysis of slotted plate fins heat sinks using numerical and experimental techniques - Altaf, K. (Elsevier Ltd, 2022)
A heatsink's thermal and hydraulic performance can be optimized by making several modifications in the geometry. Modifying the heatsinks usually increases the weight by adding material. This study focuses on enhancing heat transfer by the removal of material in the form of slots. Fabrication of slots is one of the advantageous geometric modifications in the plate fins. This study also focuses on optimizing the slots for heat transfer augmentation without compromising the pressure drop. In this study, the authors performed Computational Fluid Dynamics (CFD) analysis of various geometric iterations of the plate fins. The heat sinks with comparatively better thermal performance are pointed out (S8 and S9). On average, the Nusselt number of the heat sink S9 is 28.4 higher than the plain heatsink P at various Reynold's number values. The introduction of slots drops the pressure across the heat sinks with an additional average of 9.3 pressure drop across the heatsink S9 compared to the heatsink P at various Re number values. The authors performed an experimental analysis to validate the numerical analysis. The maximum difference between the observed and simulated bast temperature values is 2.6, 2.9, and 3 for the heat sinks P, S8, and S9, respectively. Â© 2022 The Authors.